2012
DOI: 10.1007/s10464-012-9552-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Justice and Religious Participation: A Qualitative Investigation of Christian Perspectives

Abstract: This investigation examines how self-identified Christians in the Midwest U.S. understand and work for social justice, with a focus on their process of social justice development and the role of religious congregations in promoting social justice. Using a grounded theory analysis of 15 in-depth interviews, results indicated multiple understandings of social justice such as meeting basic needs, fixing social structures and systems to create equal distributions of resources, promoting human rights and dignity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 51 publications
7
53
0
Order By: Relevance
“…For example, Bass and Avolio (1993) note that expectations for member engagement are created based on where leaders focus their energy. Qualitative research by Todd and Rufa (2013) found that congregational leaders may be vital in creating and maintaining a norm for social justice and that some congregations may sponsor specific social justice activities or programs. In the current study, we expect that people who perceive their congregation to be involved in justice activities, thus aware of a norm for justice, will be more likely to participate in justice activities through or outside the congregation.…”
Section: Norm For Justicementioning
confidence: 99%
See 2 more Smart Citations
“…For example, Bass and Avolio (1993) note that expectations for member engagement are created based on where leaders focus their energy. Qualitative research by Todd and Rufa (2013) found that congregational leaders may be vital in creating and maintaining a norm for social justice and that some congregations may sponsor specific social justice activities or programs. In the current study, we expect that people who perceive their congregation to be involved in justice activities, thus aware of a norm for justice, will be more likely to participate in justice activities through or outside the congregation.…”
Section: Norm For Justicementioning
confidence: 99%
“…In this study we examine member perceptions of if their leader confronts social injustice to understand how such modeling may encourage member social justice involvement. Other research with counseling psychology trainees (Beer et al 2012;Singh et al 2010) and religious individuals (Todd and Rufa 2013) suggests that the presence of social justice models and mentors are important to facilitate social justice engagement. Religious leaders may be particularly important as members may ascribe referent power (i.e., power based on admiration and respect, French and Raven 1959) based on the leaders religious position and perceived religious authority.…”
Section: Leader Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Item content was based on theory, qualitative research, and research on congregational collaboration (Chaves, 2004;Todd, 2012;Todd & Houston, 2013;Todd & Rufa, 2013). For providing resources to community groups, participants read the prompt, "In the last year, to what extent did your group provide time, money, volunteers, or other resources to:" and then responded on a 1 (not at all) to 6 (to a great extent) scale for each of the following four items: (a) other religious congregations to address local community issues, (b) government to address local community issues, (c) secular non-profits to address local community issues, and (d) para-church organizations to address local community issues.…”
Section: Methodsmentioning
confidence: 99%
“…The sanctification of social justice builds on this research by examining how people imbue spiritual significance to working for social justice. Research supports this link, as some people connect their religious beliefs and spirituality to working for social justice (Beer, Spanierman, Greene, & Todd, 2012;Goodman, 2000;Todd & Rufa, 2013). In the current study, we examined whether students in PCRW types associated with greater racial justice engagement also report higher levels of sanctification of social justice.…”
Section: Religious Beliefs and Pcrw Cluster Typesmentioning
confidence: 97%